Combination of anti-glycopeptidolipid-core IgA antibody and clinical features for diagnosing potential nontuberculous mycobacterium pulmonary disease in routine practice - Takuya Iwasaki; Fumihiro Yamaguchi; Makoto Hayashi; Hitoshi Kobayashi; Kento Hirata; Kenta Miyo; Chika Kondo; Mamiko Kanzaki; Kazusawa Tei; Takashi Abe; Shunsuke Sakakura; Daisuke Inoue; et al. (SAGE Journals, 2022)
Background:
The anti-Mycobacterium avium complex (MAC) antibody test measures levels of IgA antibody against the glycopeptidolipid (GPL) core in the bacterial cell walls and is a useful clinical indicator of nontuberculous mycobacterium pulmonary disease (NTM-PD). However, it is not currently possible to diagnose the disease using anti-MAC antibodies alone.
Objectives:
The study aim was to assess the efficacy of the combination of anti-MAC antibodies and clinical findings for diagnosing potential NTM-PD.
Methods:
This cross-sectional study included 938 patients tested using the anti-MAC antibody. NTM-PD was diagnosed by multiple positive cultures of the same species in sputum samples. Multivariate logistic regression models were used to identify the clinical factors related to NTM-PD.
Results:
Overall, 19.6% (184/938) of participants were diagnosed with NTM-PD. In multivariate analysis, positive anti-MAC antibodies, low body mass index, absence of malignancy, and cavity-forming lung lesions were significantly associated with NTM-PD at diagnosis. The positive rates of the anti-MAC antibody test were 79.4% (135/170) for MAC and 55.6% (5/9) for Mycobacterium abscessus complex, respectively.
Conclusions:
Bronchoscopic examinations should be performed especially in certain types of individuals from whom sputum samples cannot be obtained. Anti-MAC antibodies are also positive in patients other than those harboring MAC, but the rate may be low because of the different components in GPLs.
Keywords: 111702 Aged Health Care; 111599 Pharmacology and Pharmaceutical Sciences not elsewhere classified; 110203 Respiratory Diseases